Diffuse Leptomeningeal Glioneuronal Tumor in an Adult: A Diagnostic Challenge - Bhaskar, Mukesh Kumar; Meel, Mukta; Mathur, Kusum; Jindal, Arpita; Khandelwal, Mohit (Indian Journal of Neurosurgery, 2022)
Here we report a rare case of diffuse leptomeningeal glioneuronal tumor (DLGNT) in a 35-year-old man, who was misdiagnosed twice as having tuberculosis meningitis and later racemose neurocysticercosis. His delayed diagnosis of DLGNT might be due to prevalence of tuberculosis in our country, similarity in magnetic resonance imaging finding of prominent leptomeningeal enhancement in different cisterns of brain, and extreme rarity of DLGNT in the adults. So, it should be differentiated clinically and radiographically from granulomatous or infectious conditions. Hence, a timely histologic diagnosis through a leptomeningeal biopsy of the brain and spinal cord in case of unusual leptomeningeal enhancement with uncertain laboratory findings is essential because cytological examination of the cerebrospinal fluid in DLGNT is known to be negative.
Keywords: adult; diffuse leptomeningeal glioneuronal tumor; leptomeningeal biopsy